Exonal switch down-regulates the expression of CD5 on blasts of acute T cell leukaemia. (5th September 2017) - Rai, A K; Singh, A; Saxena, A; Seth, T; Raina, V; Mitra, D K
Summary: To date, CD5 expression and its role in acute T cell lymphoblastic leukaemia (T-ALL) have not been studied closely. We observed a significant reduction in surface expression of CD5 (sCD5) on leukaemic T cells compared to autologous non-leukaemic T cells. In this study, we have shown the molecular mechanism regulating the expression and function of CD5 on leukaemic T cells. A total of 250 patients suffering from leukaemia and lymphoma were immunophenotyped. Final diagnosis was based on their clinical presentation, morphological data and flow cytometry-based immunophenotyping. Thirty-nine patients were found to be of ALL-T origin. Amplification of early region of E1A and E1B transcripts of CD5 was correlated with the levels of surface and intracellular expression of CD5 protein. Functional studies were performed to show the effect of CD5 blocking on interleukin IL-2 production and survival of leukaemic and non-leukaemic cells. Lack of expression of sCD5 on T-ALL blasts was correlated closely with predominant transcription of exon E1B and significant loss of exon E1A of the CD5 gene, which is associated with surface expression of CD5 on lymphocytes. High expression of E1B also correlates with increased expression of cytoplasmic CD5 (cCD5) among leukaemic T cells. Interestingly, we observed a significant increase in the production of IL-2 by non-leukaemic T cells upon CD5 blocking, leading possibly to their increased survival at 48 h. Our study provides understanding of the regulation of CD5 expression on leukaemic T cells, and may help in understanding the molecular mechanism of CD5 down-regulation. Graphical Abstract: